Linguistic models of acquisition of Russian / Kazakh as a second language (Eurasian Journal of Philology Science and Education, 2018)
The changes in society, active international processes, the linguistic construction of sovereign Kazakhstan have identified increasing interests in solving the problems of mastering a second language. The CIS countries had a considerable experience of theoretical understanding of the practice of teaching Russian and Kazakh languages as a foreign language. In Kazakhstan, the practice of teaching Russian and Kazakh languages as a second language also has a great experience. The article provides an overview of the work of applied linguistic scientists of the Kazakhstani Schools on topical issues of the theory of mastering a second language. Theory of mastering a second language was developed in the works of applied linguistic scientists of Kazakhstan’s school as L.V. Ekshembaeva, Zh.A Nurshaihova, G.E. Utebalieva, I.G. Zhulamanova, A.A. Kurushzhanova etc. The purpose of this article is to describe the linguistic models of mastering a second language, developed as a result of theoretical generalization and justification of the practice of teaching of Russian and Kazakh languages as a foreign language. All models are united by methodological basis, which the author defines as cognitive and communicative